ECO-BIOLOGICAL SYSTEM MODELING - T. I. Burak; M. M. Tatur; M. M. Lukashevich; R. V. Trashcheev (Системный анализ и прикладная информатика)
The methodology for computer modeling of complex eco-biological models is presented in this paper. It is based on system approach of J. Forrester. Developed methodology is universal for complex ecological and biological systems. Modeling algorithm considers specialties of eco-biological systems and shows adequate and accurate results in practice.